Clinical case of combined malignant neoplasm of the cervix: neuroendocrine carcinoma and squamous cell cancer - T. A. Garkusha; A. N. Zagrebel'nikova; V. N. Shelepova; F. V. Alyab'ev; N. V. Khludneva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Neuroendocrine carcinomas are rare and aggressive types of cervical tumors. Available literature contains limited descriptions of mixed carcinomas, and knowledge about this type of mixed carcinoma remains limited. Morphological diagnosis of this carcinoma type can be difficult due to the fact that neuroendocrine carcinoma cells can resemble squamous cell carcinoma. Additional complications can be caused by the lack of expression of some specific neuroendocrine markers. Incorrect diagnosis of this carcinoma can lead to incorrect patient management tactics or treatment delays. This article presents a clinical observation of a 45-year-old female patient who was diagnosed with mixed neuroendocrine and squamous cell carcinoma of the cervix, HPV-associated, with multiple metastases. This case is of particular interest due to the rarity of this pathology and diagnostics challenges it presents.